Literature and spirit : essays on Bakhtin and his contemporaries - Patterson, David, 1948- (The University Press of Kentucky, 2015)
""If Bakhtin is right, "" Wayne C. Booth has said, ""a very great deal of what we western critics have spent our time on is mistaken, or trivial, or both."" In Literature and Spirit David Patterson proceeds from the premise that Bakhtin is right. Exploring Bakhtin's notions of spirit, responsibility, and dialogue, Patterson takes his reader from the narrow arena of literary criticism to the larger realm of human living and human loving. True to the spirit of Bakhtin, he draws the Russian into a vibrant dialogue with other thinkers, including Foucault, Berdyaev, Gide, Lacan, Levinas, and Heidegge.